Case report: Mandible fracture in children - Ernesto Carmona Fernández; Elier Morales Moreira; Alejandro Perez Martínez (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
The type of maxillofacial fractures in children and young adults varies with evolving skeletal anatomy and social and environmental factors. The general principles of treating mandibular fractures are the same for children and adults: Anatomic reduction along with rigid skeletal stabilization is mandatory until bone union has occurred. Here we present a female child with a fall trauma accident, presenting with fractures of the symphysis, horizontally and vertically unfavourable, with significant displacement. Open reduction and internal fixation with miniplates and screws was done, with good post-operative recovery and outcome.